Perencanaan Teknis Jaringan Pipa Distribusi Air Bersih Gampong Cot Lampoh Soh Kecematan Montasik Kabupaten Aceh Besar - Ichsan Syahputra; Mahyuddin; Lukman; Muhammad Ashraful Annam (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
Cot Lampoh Soh Village is one of the villages in Montasik District, Aceh Besar Regency, Aceh Province where Administratively Cot Lampoh Soh Village is directly adjacent to Indrapuri District, Aceh Besar Regency. This village has 166 heads of families with a population of 263 people, generally working as farmers and some as civil servants and private sector, and is dominated by the age of 25 to 59 years with a total of 121 people and most work as farmers as much as 78.90%, the number of family members ranges from 1 to 5 people per head of family or 5.30% to 26.30%. As many as 78.90% use shallow wells. Cot Lampoh Soh Village has 1 drilled well point located in Meunasah, where the drilled well water is used by the community only for ablution water needs and the needs of meunasah gampong activities. The projected population for the next 30 years from 2025 is 263 people to 467 people in 2054, the population growth rate is assumed to be 2% per year, the water requirement per person is 150 liters/person/day, water loss is assumed to be 10%, the water requirement in 2054 is 0.73 liters/second. The planned pipe types are HDPE with a diameter of 90 mm with a length of 447 meters and HDPE with a diameter of 63 mm with a length of 605 meters with a total length of 1052 meters. The form of Community Service (PKM) activities carried out by the Author in the UNAYA KKN activities for the Even Semester 2024/2025 is the Technical Planning of the Clean Water Distribution Pipeline Network for Gampong Cot Lampoh Soh where the water source to be used is drilled well water located in Meunasah Gampong. The output of this activity is to create a technical planning product consisting of a Design Drawing and Budget Plan for the Construction of a Clean Water Pipeline Network to support improving community health by utilizing the existing drilled water source in the Meunasah Gampong Cot Lampoh Soh as the center of community activities in Gampong Cot Lampoh Soh, Montasik District, Aceh Besar Regency.